A differential analysis for men and women's determinants of livelihood diversification in rural rain-fed region of Pakistan: An ordered logit model (OLOGIT) approach. Issue 1 (2022) - Habib, Nusrat; Alauddin, Mohammad; Cramb, Rob; Rankin, Peter
Abstract: Gender responsiveness is a crucial element in achieving inclusive economic and developmental growth of an economy. A gender-differentiated analysis in determining livelihood diversification strategies is, therefore, important for developing gender sensitive policies. The study examined and presented the determinants of livelihood diversification for men and women smallholders' households in rural Pakistan. A multistage data sampling technique was used in selection and collection of the data from 148 men and 147 women households. Considering the three types of ordered structured dependent variable of livelihood strategies preferences (LC1, LC2 and LC3) ordered logit model (OLOGIT) was applied. The results revealed that there were some similarities and some differentials among men and women's for determining livelihood diversification strategies. The first differential was based on signs of the coefficients such as natural disasters, access to public transport and women role in building social relations showed varied nature of response for men and women. The second differential was explored on the basis of statistical significance levels, that revealed the factors that were highly significant for men seems to be non-significant for women and vice versa scenarios existed for most of the determinants of livelihood strategies. Like, the factors family labor, membership in any organization, social linkages, access to latest machinery and accessibility of credit were highly significant for men but non-significant for women. While only education, and family labor were the common significant factors in diversification. The role of formal financial institution was lacking in the study. Women's major livelihood sources was LC1-(on-farm) while men were more towards LC2-(off-farm) and LC3-(Non-farm) strategies. These differentials highlight the importance of a policy initiative to be taken to increase access and availability of assets and services to women households, improve their capacity to participate in non-farm sectors, and accelerate transformative changes at both local and policy levels.